Methods For Developing 4k Skills In Students Based On The Steam Educational Program - Qahhorjonova Q. F. (Euro Asian Journal Publishing, 2024)
The article discusses methods for developing 4K skills in students based on the STEAM educational program
Keywords: analytical; creative; technology